Phylogeography of the shanny Lipophrys pholis (Pisces: Blenniidae) in the NE Atlantic records signs of major expansion event older than the last glaciation - Francisco, Sara Martins (2012)
The study of the phylogeography of inshore fish from West Europe is revealing diverse geographical and demographical patterns. Some species conform to the phylogeographic patterns typical of terrestrial organisms, with marked signatures of the last glaciation and a decline of genetic diversity to the north of the species range. Other species, however, reveal no decline in diversity with latitude and signatures of expansions older than the last glaciation. The shanny Lipophrys pholis is a common intertidal resident fish in west European rocky shores. It is unable to leave the rocky stretch where it settled as a juvenile, so that dispersal depends entirely on the planktonic larval stage. These life-history and behavioural traits make the shanny an interesting species for phylogeographical analysis, as long-range movements by adults, which could blur historical signals, are absent. In this paper the phylogeography of L. pholis was studied using a fragment of the mitochondrial control region and one from the first intron of the S7 ribosomal protein gene. The European samples (ranging from SW Spain to the Netherlands) did not display population differentiation, isolation-by-distance or latitudinal declines in genetic diversity. Iberia was proposed as having operated as the main glacial refugium for the shanny. The genealogy of the European population showed that the largest expansion detected was older than the last glaciation, with lineages persisting from the early Pleistocene, which does not conform to colonisation by a few founders in the current interglacial. It is argued that if fishes have very large population sizes and high dispersal rates, populations can efficiently track climatic shifts so that little or no genetic structure remains after each range expansion and latitudinal gradients of genetic diversity tend to be weak or non-existent.